Analisis Penggunaan Bahasa Indonesia pada Saluran YouTube Gadgetin Sebagai Upaya Promosi Brand Handphone VIVO - Nur Azizah, Kharisma; Saptono Hadi; Lailiyatus Sa’diyah; Agus Hermawan (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
Analysis of the use of Indonesian on the gadgetin Youtube channel as an effort to promote the Vivo mobile phone brand. Analysis is a very intensive examination process in a research object. Indonesian is the official language in Indonesia, which is used by the Indonesian population as a means of daily communication. An analysis of the use of Indonesian is an analysis that describes observational studies of various aspects of language, including grammar, vocabulary, phonology, morphology, syntax, and pragmatics. The gadgetin youtube channel is a channel that focuses on reviewing information about technology that discusses various of the latest technology products. Promotion is a way to increase sales. The vivo mobile phone brand is one of the mobile phone brands originating from China. The method used is qualitative descriptive. Qualitative descriptive is research that aims to describe and understand a more in-depth situation. This data collection technique is from listening to youtube broadcasts, recording, analyzing. The purpose of the study is to examine the use of Indonesian on the Gadgetin Youtube Channel as an effort to promote the Vivo mobile phone brand.